Early Detection of Foot‐And‐Mouth Disease Virus from Infected Cattle Using A Dry Filter Air Sampling System. Issue 2 (25th August 2015) - Pacheco, J. M.; Brito, B.; Hartwig, E.; Smoliga, G. R.; Perez, A.; Arzt, J.; Rodriguez, L. L.
Summary: Foot‐and‐mouth disease (FMD) is a highly contagious livestock disease of high economic impact. Early detection of FMD virus (FMDV) is fundamental for rapid outbreak control. Air sampling collection has been demonstrated as a useful technique for detection of FMDV RNA in infected animals, related to the aerogenous nature of the virus. In the current study, air from rooms housing individual ( n = 17) or two groups ( n = 4) of cattle experimentally infected with FDMV A24 Cruzeiro of different virulence levels was sampled to assess the feasibility of applying air sampling as a non‐invasive, screening tool to identify sources of FMDV infection. Detection of FMDV RNA in air was compared with first detection of clinical signs and FMDV RNA levels in serum and oral fluid. FMDV RNA was detected in room air samples 1–3 days prior (seven animals) or on the same day (four animals) as the appearance of clinical signs in 11 of 12 individually housed cattle. Only in one case clinical signs preceded detection in air samples by one day. Overall, viral RNA in oral fluid or serum preceded detection in air samples by 1–2 days. Six individually housed animals inoculated with attenuated strains did not show clinical signs, but virus was detected in air in one of these cases 3 days prior to first detection in oral fluid. In groups of four cattle housed together, air detection always preceded appearance of clinical signs by 1–2 days and coincided more often with viral shedding in oral fluid than virus in blood. These data confirm that air sampling is an effective non‐invasive screening method for detecting FMDV infection in confined to enclosed spaces (e.g. auction barns, milking parlours). This technology could be a useful tool as part of a surveillance strategy during FMD prevention, control or eradication efforts.